Syarat Subjektif dan Objektif Sahnya Perjanjian dalam Kaitannya dengan Perjanjian Kerja - Suwarti Suwarti; Faissal Malik (Khairun Law Journal, 2018)
The Law of the Republic of Indonesia Number 13 Year 2003 regarding Manpower explicitly stipulates that an employment agreement is made on the basis of: (i) an agreement between the two parties, (ii) the ability or ability to perform legal actions, (iii) the existence of the promised work, and ( iv) the work promised is not contrary to public order, decency, and applicable laws and regulations. Based on these provisions, which include subjective conditions for the validity of the work agreement are: (i) agreement between the two parties, (ii) the ability or ability to do the agreement is not contrary to public order, decency, and applicable laws and regulations. The legal implications for the work agreement can be canceled, while the work agreement that does not meet the objective objectives of the validity of the employment agreement is that the employment agreement is null and voidThe Law of the Republic of Indonesia Number 13 Year 2003 regarding Manpower explicitly stipulates that an employment agreement is made on the basis of: (i) an agreement between the two parties, (ii) the ability or ability to perform legal actions, (iii) the existence of the promised work, and ( iv) the work promised is not contrary to public order, decency, and applicable laws and regulations. Based on these provisions, which include subjective conditions for the validity of the work agreement are: (i) agreement between the two parties, (ii) the ability or ability to do the agreement is not contrary to public order, decency, and applicable laws and regulations. The legal implications for the work agreement can be canceled, while the work agreement that does not meet the objective objectives of the validity of the employment agreement is that the employment agreement is null and void